First Report on Bioaccessibility, Antioxidant Activity and Total Phenolic Compounds From Stachys thirkei C.Koch Using A Simulated In Vitro Digestion System - Gorkem Dulger; Emine Aydın; Pınar Göç Rasgele (Journal of Advanced Research in Natural and Applied Sciences, 2022)
It is of great importance to determine the antioxidant properties of plants, especially those used for food, pharmacology and medicinal purposes. Stachys thirkei C.Koch belonging to Lamiaceae family is used as a medicinal aromatic plant in Turkey. The present study was carried out to investigate the total phenolic contents, antioxidant activity and bioaccessibility of S. thirkei C.Koch. The total phenolic content (TPC) was evaluated by Folin-Ciocalteu colorimetric procedure and antioxidant activity determine four distinctive methods (ABTS•+, CUPRAC, DPPH• and FRAP). According to the results, the levels of hydrolysable phenolics (1538.99±4.57 mg of GAE/100g) approximately three and a half fold higher than extractable phenolics (422.96±4.70 mg of GAE/100g). The TPC of S. thirkei C.Koch was determined to be 1961.95±4.46 mg of GAE/100g. On the other hand, the bioaccessible fractions and phenolic bioaccessibility of S. thirkei C.Koch were found to be 1766.72±2.96 μmol Trolox/g and 90.05±1.50%, respectively. At the same time, the antioxidative bioaccessibility of S. thirkei was found to be higher in FRAP method (1164.29 μmol Trolox/g) and also the bioaccessibility (%) of S. thirkei C.Koch was found to be higher in CUPRAC method (93.41%). Present study is the first report to investigate the antioxidant effect and bioaccessibility of the extracts from S. thirkei C.Koch. The results of the present study can be strong scientific proof to use this plant as a beneficial source of antioxidant referments and the studies can be further extended to investigate whether they exhibit similar activities in in vivo systems.